Examining the lived realities of street vendors in Iloilo City in the time of COVID-19 Arnie Joy J. Table and Mariah Diether Gale T. Yatar.. - Table, Arnie Joy J.
This phenomenological study explores the lived realities of semi-fixed non-food street vendors in J.M. Basa St., Iloilo City in the time of the COVID-19 pandemic. It provided an overview of the state of street vending in Iloilo City which includes the typology of street vendors, the policies and programs, and the types of support provided to street vendors. Lived realities are described through the working conditions, challenges, and coping strategies in street vending. Data were collected through semi-structured interviews, key informant interview, ocular observation, and secondary data review. Research findings were analyzed using the Interpretative Phenomenological Analysis to investigate the lived realities of the street vendors and draw out development implications to alleviate their situation. The study revealed that street vending is characterized by an unstable income, long working hours, and lack of social security. Along with these economic difficulties are the urban displacement and the physical challenges encountered by street vendors. The study also provides recommendations to integrate street vendors in urban planning for genuine representation, to improve their working conditions, to provide adequate workspace, access to financial support; and lastly, to pursue related studies on street vending in the local context.